Legitimasi Hukum dan Ketimpangan Gender dalam Isbat Nikah Anak: Studi Putusan PA Tasikmalaya Nomor 283/Pdt.P/2024/PA.Tmk - Titing Oting Supartini; Yayan Rahtikawati; Supriati Rumagia (al-Battar: Jurnal Pamungkas Hukum, 2025)
Marriages that are not officially registered are still a legal issue in Indonesia, especially when it involves minors. This research aims to analyze the Decision of the Tasikmalaya City Religious Court Number 283/Pdt.P/2024/PA. Tmk related to the application for isbat nikah involving child marriage, reviewed from a legal and gender perspective. The research method used is a normative juridical approach with the study of judgments as the main object of analysis, complemented by a review of the legal and gender literature. The results of the study show that legally, the ruling provides legitimacy to the marital status and legal protection for children born of the marriage. However, from a gender perspective, this case reflects the weak implementation of protection for girls, in the midst of efforts to increase the minimum age of marriage through Law Number 16 of 2019. The discussion highlighted the negative impact of child marriage on women, including limited access to education, increased reproductive health risks, and unequal power relations in households. These findings underscore the urgency of strengthening regulations related to marriage dispensation and the need for comprehensive legal education to prevent the practice of child marriage and ensure the protection of women's and children's rights in a fair manner.